Organizational Citizenship Behavior (OCB) in the Management of Situ Leutik Tourist Attraction by the Disporta of Banjar City Government - Nyi Raden Ruyani; Lia Muliawaty; Fitri Farizah; M. Yusuf Ibrahim (International Journal of Tourism and Hospitality in Asia Pasific, 2025)
Community-based tourism management requires the active role of the community and managers in creating a harmonious and productive work environment. Organizational citizenship behavior (OCB) is an important factor in increasing the effectiveness of tourism management, especially in the Situ Leutik tourist attraction, Banjar City. This study aims to analyze the role of OCB in the management of the Situ Leutik tourist attraction using a descriptive qualitative approach. Data were collected through observation, in-depth interviews, and literature studies. The results of the study indicate that five dimensions of OCB, namely altruism, prudence, sportsmanship, politeness, and civic virtue, play a role in improving the quality of tourism services. The community voluntarily helps visitors, maintains cleanliness, and demonstrates a professional attitude in interacting with tourists. However, there are still obstacles to community participation in tourism management decision-making. The conclusion of the study confirms that strengthening OCB behavior through increasing manager capacity and community involvement can increase the effectiveness of tourism management. Therefore, local governments need to implement more inclusive policies to support the sustainability of community-based tourism.